2007
DOI: 10.1016/j.stam.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Fine yellowα-SiAlON:Eu phosphors for white LEDs prepared by the gas-reduction–nitridation method

Abstract: Yellow-emitting a-SiAlON:Eu 2+ phosphors were synthesized by the gas reduction and nitridation of a homogeneous oxide precursor in a CaO-Al 2 O 3 -SiO 2 -Eu 2 O 3 system at 1400-1450 1C using an NH 3 -CH 4 mixture gas as a reduction-nitridation agent. The precursor was prepared by a sol-gel process using a low-cost nitrate, tetraethyl orthosilicate and citric acid as the starting materials. The effects of reaction parameters such as heating rate, temperature, holding time and CH 4 content on the composition, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 17 publications
(37 reference statements)
1
35
0
1
Order By: Relevance
“…[201] In den letzten Jahren erhielten SE-aktivierte a-SiAlONe (vor allem Eu 2+ -dotierte) viel Aufmerksamkeit als Lumineszenzmaterialien, da ihre Photolumineszenz-Eigenschaften über die Zusammensetzung des a-SiAlON-Wirtsgitters oder die Eu 2+ -Konzentration beeinflusst werden kçnnen. [202][203][204] Intensiv geforscht wurde an Eu 2+ -dotiertem Ca-a-SiAlON, das eine einzelne intensive Breitband-Emission bei 583-603 nm zeigt [205] sowie an dotiertem Li-a-SiAlON, dessen Emission durch Verändern der Al/Si-oder O/N-Verhältnisse des Wirtsgitters oder über die Eu 2+ -Konzentration über einen breiten Bereich von 563-586 nm abgestimmt werden kann. [206] Hirosaki et al beschrieben einen Eu 2+ -aktivierten, grün emittierenden b-SiAlON-Leuchtstoff, der Intensitätsmaxima im Bereich 528-550 nm aufweist und eine geringe thermische .…”
Section: Lumineszenzunclassified
“…[201] In den letzten Jahren erhielten SE-aktivierte a-SiAlONe (vor allem Eu 2+ -dotierte) viel Aufmerksamkeit als Lumineszenzmaterialien, da ihre Photolumineszenz-Eigenschaften über die Zusammensetzung des a-SiAlON-Wirtsgitters oder die Eu 2+ -Konzentration beeinflusst werden kçnnen. [202][203][204] Intensiv geforscht wurde an Eu 2+ -dotiertem Ca-a-SiAlON, das eine einzelne intensive Breitband-Emission bei 583-603 nm zeigt [205] sowie an dotiertem Li-a-SiAlON, dessen Emission durch Verändern der Al/Si-oder O/N-Verhältnisse des Wirtsgitters oder über die Eu 2+ -Konzentration über einen breiten Bereich von 563-586 nm abgestimmt werden kann. [206] Hirosaki et al beschrieben einen Eu 2+ -aktivierten, grün emittierenden b-SiAlON-Leuchtstoff, der Intensitätsmaxima im Bereich 528-550 nm aufweist und eine geringe thermische .…”
Section: Lumineszenzunclassified
“…Ca--SiAlON:Eu 2+ phosphor shows a strong absorption in the UV-visible spectral region and exhibits intense yellow emission in range of 570-600 nm, making it an attractive wavelength-conversion phosphor for white light-emitting diodes (LEDs) when coupled with a blue GaN-based chip [4,5]. Thus, in recent years -SiAlON has been investigated extensively as a host material for phosphors [4][5][6][7][8][9][10][11]. Generally, Ca--SiAlON:Eu 2+ phosphors are synthesized at some unusual conditions, such as high firing temperature and high nitrogen gas pressure (1750°C, 0.5 MPa).…”
mentioning
confidence: 99%
“…Generally, Ca--SiAlON:Eu 2+ phosphors are synthesized at some unusual conditions, such as high firing temperature and high nitrogen gas pressure (1750°C, 0.5 MPa). Up to date, three major synthetic methods have been used to synthesize Ca--SiAlON:Eu 2+ phosphors: solid-state reaction [6], gas-reduction nitridation (GRN) [7], and carbothermal reduction and nitridation (CRN) [8]. The gaspressure sintering (GPS) method is a prevailing method for synthesizing Ca--SiAlON:Eu 2+ , which requires elevated temperature and high nitrogen gas protection, as well as high-purity nitrides as starting materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The necessity of high-temperature post-annealing remains as a technological drawback of this process. A recent report showed that such post-annealing can be avoided [21], and further optimization in this direction is desirable. Combustion synthesis is a promising method particularly for low ignition temperature, short time consumption and direct crystallization of small-sized particles [22][23][24].…”
Section: Introductionmentioning
confidence: 99%